2022
DOI: 10.3389/fbinf.2022.1044975
|View full text |Cite
|
Sign up to set email alerts
|

Advances in antibody discovery from human BCR repertoires

Abstract: Antibodies make up an important and growing class of compounds used for the diagnosis or treatment of disease. While traditional antibody discovery utilized immunization of animals to generate lead compounds, technological innovations have made it possible to search for antibodies targeting a given antigen within the repertoires of B cells in humans. Here we group these innovations into four broad categories: cell sorting allows the collection of cells enriched in specificity to one or more antigens; BCR seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…Assessing the antibody and epitope specificity of antibodies elicited by a particular immune perturbation is of paramount importance for the development of therapeutic antibodies and the study of immune responses to disease or vaccination ( 35 ). However, this is a non-trivial task due to the diverse nature of antibody responses across donors ( 1 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the antibody and epitope specificity of antibodies elicited by a particular immune perturbation is of paramount importance for the development of therapeutic antibodies and the study of immune responses to disease or vaccination ( 35 ). However, this is a non-trivial task due to the diverse nature of antibody responses across donors ( 1 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the DTP analysis suggested that provisional assignment of antigen specificities using FACS can itself be a source of error. Although antigen sorting could differentiate between positive and negative B cells, antigen specificities were less reliable, probably due to the non-specific binding of fluorophores, streptavidin, or antigen purification tags ( 35 , 36 ). Double-fluorescent antigen-tagging techniques ( 37 ) or conjugation with sequencing-readable barcodes, as demonstrated in LIBRA-seq ( 38 ), have the potential to increase the confidence in antigen-specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Such methods are labor-and time-intensive ways of identifying antigen-specific antibodies. Mapping sequences to well-known established antibody CDR3 information can provide templates or blueprints to identify important antibody genes in a distinct set of individual populations, antibody discovery, and vaccine response evaluation without the need for antigen-specific sorting (40). Similar methodologies have been used successfully to identify potent antibodies against Dengue, HIV-1, SARS-CoV-2, and influenza (41).…”
Section: Discussionmentioning
confidence: 99%